New voices in an old flower (SolySombra Recordings Production, 2016)
"It was visionary, the awakening of a new era," says Amha Eshete, the Ethiopian musical producer in the days of Swingin'Addis, the golden age. Recordings made between the 50s and the 80s, the Ethiopian music publications that crossed borders; while the contemporary musical scene of Addis Ababa remains practically unknown to the world. Music in Addis Ababa expresses everyday life and the processes of transformation in the city. This documentary explores this musical vitality as it observes the plurality of the city and its inhabitants. --